2015
DOI: 10.1128/jvi.00560-15
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Recruitment of UAF1-USP Complexes by a PHLPP1-E1 Chimeric Helicase Enhances Human Papillomavirus DNA Replication

Abstract: The E1 helicase from anogenital human papillomavirus (HPV) types interacts with the cellular WD repeat-containing protein UAF1 in complex with the deubiquitinating enzyme USP1, USP12, or USP46. This interaction stimulates viral DNA replication and is required for maintenance of the viral episome in keratinocytes. E1 associates with UAF1 through a short UAF1-binding site (UBS) located within the N-terminal 40 residues of the protein. Here, we investigated if the E1 UBS could be replaced by the analogous domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
(73 reference statements)
2
8
0
Order By: Relevance
“…These results showed that the E1-UAF1 interaction is required for the replication of HPV11 episomes in U2OS cells, similarly to what has been observed previously for HPV31 in immortalized keratinocytes ( 11 14 ). Importantly, the results also revealed that the deubiquitinating activity of USP1 is essential for episomal replication of the HPV11 genome.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…These results showed that the E1-UAF1 interaction is required for the replication of HPV11 episomes in U2OS cells, similarly to what has been observed previously for HPV31 in immortalized keratinocytes ( 11 14 ). Importantly, the results also revealed that the deubiquitinating activity of USP1 is essential for episomal replication of the HPV11 genome.…”
Section: Resultssupporting
confidence: 89%
“…Also, the previously described transcription map of the HPV11 genome in U2OS cells is similar to the transcription map of the HPV11 genome in HPV-associated lesions ( 47 ), further validating the use of the U2OS cell line to study the replication of HPV episomes. The importance of the E1-UAF1-USP1 complex for efficient HPV replication has been previously reported ( 11 14 ); however, we demonstrated that the lower replication efficiency of mutant HPV11 genomes encoding a E1 protein defective for UAF1-binding is associated with decreased production of RIs generated by the unidirectional mechanism, while bidirectional theta replication was affected to a lesser degree ( Fig. 2 ).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The effect of FGFR3 kinase activity on E2-stimulated viral DNA replication was subsequently evaluated using C33A cells transfected with BPV-1 E1 and E2 expression vectors, along with a BPV-1 luciferase-linked reporter in the presence of FGFR3 WT, K650E, and K508R expression constructs. In this assay, luciferase expression is proportional to episomal copy number and is sensitive to DNA replication inhibitors (24)(25)(26). Firefly luciferase readout was normalized to Renilla luciferase levels as a transcription and transfection control (Fluc/Rluc).…”
Section: Figmentioning
confidence: 99%
“…HPVs have been shown to recruit numerous cellular repair factors to their replication centers, mainly for HPV amplification [ 59 61 ]. Similarly, HPV E1 has been shown to interact with USP1-UAF1 complex to facilitate viral replication [ 62 ]. We speculate that increased Ub-FancD2 and foci formation may create an environment where FA repair proteins are readily available to support HPV replication.…”
Section: Discussionmentioning
confidence: 99%